Tuning the electronic structure of PtRu bimetallic nanoparticles for promoting the hydrogen oxidation reaction in alkaline media. Issue 10 (13th September 2019) - Long, Chang; Wang, Kun; Shi, Yanan; Yang, Zhongjie; Zhang, Xiaofei; Zhang, Yin; Han, Jianyu; Bao, Yini; Chang, Lin; Liu, Shaoqin; Tang, Zhiyong
Abstract : Alloying degree of PtRu bimetallic nanoparticles can be controlled to finely tune electronic effect for enhanced Hydrogen oxidation reaction in alkaline. Abstract : Optimization of the hydrogen binding energy by controlling the surface electronic structure of electrocatalysts is of great significance in the hydrogen oxidation reaction (HOR) in alkaline electrolytes. Herein, we demonstrated that the surface electronic structure of PtRu bimetallic nanoparticles could be finely tuned through the alloying degree; this led to enhanced HOR performance in an alkaline solution. The optimized Pt0.65 Ru0.35 with high alloying degree exhibited the exchange current density of 4.16 A m −2, which was about 1.5 and 2.2 times those of Pt0.74 Ru0.26 with a low alloying degree (2.75 A m −2 ) and Pt/C (1.89 A m −2 ), respectively.